Utilization of biogas as a source of electrical energy to support energy independent cages for dairy Cattle Farmers Group Sumber Sari, Ngablak, Magelang - Budi Waluyo; Bambang Pujiarto; Rochiyati Murniningsih; Sofyan Kurniawan; Husni Rakhmawan Fatoni; Dimas Riki Romadhon (Universitas Muhammadiyah Magelang, 2022)
The high monthly costs associated with the use of electrical energy for the production of dairy cowsheds at the KTT Sumber Sari, as well as the problem of PLN blackouts, have a negative impact on the smooth production process. Meanwhile, KTT Sumber Sari already has a 40 m3 biodigester that has only been used for household cooking. Problem identification, socialization, product development, and modification are the methods used in this program. The problem that has been solved as a result of this community service program is the provision of a biogas-fueled electric generator with a capacity of 5 kWatt. To optimize the performance of the engine driving the electric generator, a few changes were made to the standard gasoline-fueled genset propulsion engine, including the construction of the fuel intake and the adjustment of the combustion chamber compression pressure. The KTT Sumber Sari, can use this capacity to support energy-independent cages.